Carrier-like plate for HDI (High Density Interconnection) process and preparation method and application of carrier-like plate
By combining modified resins and modified hexagonal boron nitride and alumina gels, a carrier plate for HDI process was prepared, which solved the shortcomings of existing substrates in terms of heat resistance, thermal expansion coefficient, thermal conductivity and dielectric properties, and achieved the performance requirements of high-frequency and high-speed electronic products.
Patent Information
- Application Number
- CN202411886390.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
The existing epoxy resin/glass fiber cloth composite substrates have problems such as insufficient heat resistance, high thermal expansion coefficient, poor thermal conductivity and poor dielectric performance in electronic packaging, which is difficult to meet the needs of high-frequency and high-speed electronic products.
By combining modified BT resin with o-methylphenol epoxy resin, and adding modified hexagonal boron nitride and alumina gel, a carrier plate for HDI process was prepared. The substrate is made of a copper-clad foil substrate by impregnation, baking and hot pressing of glue and fiberglass cloth.
It has achieved excellent heat resistance, low thermal expansion coefficient, high thermal conductivity and low dielectric properties of the substrate, and has high strength and small plate bends, which can meet the demand for high frequency and high speed of electronic products.
Smart Images

Figure CN119613958A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a carrier-like substrate for HDI process and a preparation method and application thereof. Background Art
[0002] Substrates play an extremely important role in the entire electronic packaging field. Substrates mainly provide mechanical support and protection for chips and components, as well as heat dissipation and insulation. The performance of the substrate affects the level of IC manufacturing.
[0003] At present, the most widely used copper clad laminate resin system in the market is the epoxy resin system. Epoxy resin / glass cloth composite substrates are widely used in packaging carrier substrate materials due to their low cost, excellent processability, good dimensional stability and adhesion. However, epoxy resin / glass cloth composite substrates have the following defects: 1) insufficient heat resistance; 2) high thermal expansion coefficient; 3) insufficient thermal conductivity; 4) poor dielectric properties.
[0004] High frequency and high speed are the development direction of electronic packaging technology, which leads to the overall size of chips and their packaging structures becoming smaller and smaller, and the phenomenon of local heat accumulation becomes more serious, which puts more stringent requirements on the substrate materials used in electronic packaging.
[0005] Based on this, the present invention designs a carrier-like substrate for HDI process and a preparation method and application thereof to solve the above problems. Summary of the invention
[0006] In view of the above shortcomings of the prior art, the present invention provides a substrate for HDI process and its preparation method and application, aiming to solve the problem that the IC packaging substrates on the market cannot simultaneously meet the requirements of electronic products such as excellent heat resistance, low thermal expansion coefficient, high thermal conductivity and low dielectric constant.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A carrier-like substrate for HDI process, wherein BT resin (bismaleimide-triazine resin) and o-methylphenolic epoxy resin are compounded and modified as the main resin of the substrate, and modified hexagonal boron nitride and alumina gel are added to the resin system to make glue; then the glue and glass fiber cloth are impregnated and baked to obtain a prepreg, and finally the prepreg is subjected to hot pressing to obtain a copper-clad substrate for a carrier-like substrate for HDI process;
[0009] The glue comprises the following raw materials in parts by weight: 700-782 parts of BT resin, 285-334 parts of o-methylphenolic epoxy resin, 453-551 parts of PPO powder, 402-435 parts of solvent A, 450-472 parts of solvent B, 584-613 parts of hexagonal boron nitride and alumina gel, 5-7 parts of coupling agent, 2-4 parts of EPDM rubber, and 4-7 parts of accelerator;
[0010] The hexagonal boron nitride and alumina gel comprises the following raw materials in parts by weight: 138-145 parts of hexagonal boron nitride, 12-13 parts of alumina, 71-102 parts of 10.8-13.6w% sodium alginate aqueous solution, 210-249 parts of 10-15w% calcium chloride aqueous solution, 50-75 parts of 25-34w% citric acid aqueous solution, and 25-38 parts of polyethyleneimine.
[0011] Furthermore, the preparation method of the hexagonal boron nitride and alumina gel is as follows: grinding the hexagonal boron nitride and alumina to nanoscale and dispersing them in a sodium alginate aqueous solution, then dripping the mixture dropwise into a calcium chloride aqueous solution under stirring conditions, and adding polyethyleneimine in 3 to 5 times, and cross-linking reaction for 2.5 to 3.3 hours; then rinsing the surface of the gel microbeads with deionized water for 2 to 3 times, using a citric acid aqueous solution to evenly spray the surface of the gel microbeads, and finally drying at a low temperature of 55 to 65°C to obtain the hexagonal boron nitride and alumina gel microbeads.
[0012] Furthermore, the promoter is 2E4MZ, the solvent A is PM, the solvent B is toluene, and the coupling agent is titanate coupling agent.
[0013] In order to better achieve the purpose of the present invention, the present invention also provides a method for preparing the carrier-like substrate for HDI process, comprising the following steps:
[0014] Step 1: Preparation of glue;
[0015] (1) Preparation of hexagonal boron nitride and alumina gel
[0016] Grind hexagonal boron nitride and alumina to nanometer scale and disperse them in sodium alginate aqueous solution, then drip the mixture drop by drop into calcium chloride aqueous solution under stirring conditions, and add polyethyleneimine in 3 to 5 times, and cross-link for 2.5 to 3.3 hours; then rinse the surface of the gel microbeads with deionized water, spray the surface of the gel microbeads with citric acid aqueous solution, and finally dry to obtain hexagonal boron nitride and alumina gel microbeads;
[0017] (2) Dispersion of hexagonal boron nitride and alumina gel
[0018] First, inject solvent A into the reactor, stir at high speed, add hexagonal boron nitride and alumina gel, and stir while adding. Start timing after the addition is completed, stir for more than 1 hour, the dispersion temperature is 30-45℃, and the pressure is normal;
[0019] (3) Resin tank: Solvent B, BT resin, o-methylphenolic epoxy resin, EPDM rubber, and PPO powder are then pumped into the reactor;
[0020] (4) Fixing reaction: Add the accelerator and coupling agent into the reaction kettle, control the reaction temperature at 30-45°C, and continue to stir at high speed for 4.5-5 hours to allow them to fully react with the above resin to produce a curing reaction;
[0021] (5) Stop the machine to measure S / G: Draw an appropriate amount of glue liquid and test whether the S / G of the glue is between 280 and 320S. If so, the glue quality is qualified;
[0022] Step 2: Preparation of prepreg;
[0023] The glass fiber cloth is immersed in the prepared glue and then dried to obtain a semi-solid sheet with appropriate parameters;
[0024] Step 3: Preparation of copper clad substrate for carrier-like substrate for HDI process;
[0025] The multi-layer prepreg and copper foil are stacked and placed in a hot press for hot pressing. The prepreg is hot pressed to melt the resin in the prepreg and drive out the bubbles under high pressure, so that the resin gradually hardens and adheres to the copper foil.
[0026] Furthermore, the high-speed stirring speed is controlled at 1000-2000 r / min.
[0027] Furthermore, in step (1), the surface of the gel microbeads is rinsed with deionized water for 2 to 3 times, a citric acid aqueous solution is evenly sprayed on the surface of the gel microbeads, and finally dried at a low temperature of 55 to 65° C. to obtain hexagonal boron nitride and alumina gel microbeads.
[0028] Furthermore, step 2 is specifically as follows: placing the electronic-grade glass fiber cloth on the cloth rack of the impregnation machine, controlling its advancement by tension, passing the electronic-grade glass fiber cloth through the impregnation tank with glue, and the electronic-grade glass fiber cloth soaked in glue enters the oven, controlling the oven temperature to 180-240° C., and obtaining a semi-cured sheet after drying.
[0029] Furthermore, the hot pressing treatment temperature in step 3 is 200-240° C. and the pressure is 1.8-3.0 MPa.
[0030] In order to better achieve the purpose of the present invention, the present invention also provides a carrier-like substrate for HDI process prepared by the above preparation method.
[0031] In order to better achieve the purpose of the present invention, the present invention also provides an application of a carrier-like board for an HDI process in preparing a carrier-like board for a 5G high-speed HDI process.
[0032] Compared with the prior art, the present invention has the following beneficial effects: the present invention first prepares hexagonal boron nitride and alumina gel, disperses hexagonal boron nitride and alumina in a sodium alginate aqueous solution, then drips them into a calcium chloride aqueous solution, and simultaneously adds polyethyleneimine for cross-linking reaction, so that hexagonal boron nitride, alumina and sodium alginate, calcium chloride, and polyethyleneimine are modified to form gel microbeads with an enhanced network structure, rinses the surface of the gel microbeads, and then uses a citric acid aqueous solution to evenly spray the surface of the gel microbeads, so that the citric acid coordinates with the metal ions on the surface of the network structure of the gel microbeads to form a stable complex, and then the obtained hexagonal boron nitride and alumina gel is dispersed into a resin system. , adding titanate coupling agent to carry out sufficient curing reaction; then preparing a semi-cured sheet, and then preparing a copper-clad foil substrate for a carrier-like substrate for HDI process; the prepared copper-clad foil substrate for a carrier-like substrate for HDI process can simultaneously meet the requirements of electronic products for excellent heat resistance (reaching the level of high Tg packaging substrate), low thermal expansion coefficient, high thermal conductivity (thermal conductivity can reach 1.98W / mk) and low dielectric (dielectric constant Dk is minimum 3.5, dielectric loss Df is minimum 0.003) and other requirements, and has high strength (peel strength is maximum 1.99N / mm, bending strength is maximum 318.5MPa), and small board warping (board warping is minimum 0.13mm). BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 The present invention is a flow chart of the preparation method of hexagonal boron nitride and alumina gel.
[0035] Figure 2 The present invention is a flow chart of a method for preparing a carrier-like substrate for use in an HDI process. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] BT resin (bismaleimide-triazine resin): has high heat resistance, low thermal expansion coefficient, low water absorption, low dielectric constant and dielectric loss and other properties.
[0038] o-Methylphenolic epoxy resin: has excellent adhesion, flexibility and heat resistance.
[0039] PPO powder (polyphenylene ether): has lower dielectric constant and loss factor.
[0040] Promoter: 2E4MZ, has high reaction promoting stability and acts as a catalyst.
[0041] Hexagonal Boron Nitride: High thermal conductivity filler, the thermal conductivity of the monomer reaches 100W / mk.
[0042] Alumina: High thermal conductivity filler, the thermal conductivity of a single body reaches 25W / mk.
[0043] Solvent A: PM (propylene glycol methyl ether), plays a role in adjusting the viscosity of the glue and is conducive to better dispersion of the filler.
[0044] Solvent B: Toluene, used to dissolve BT resin.
[0045] Coupling agent: Titanate coupling agent, improves the interface interaction between inorganic fillers and organic polymers, and improves the performance and processability of the material.
[0046] Sodium alginate: Introducing the combined structure of hexagonal boron nitride and alumina, the network structure is cross-linked with the calcium alginate molecular chain through the hexagonal boron nitride and alumina network structure to enhance the network structure;
[0047] Citric acid: coordinates with metal ions on the surface of the network structure to form a stable complex;
[0048] Polyethyleneimine: Enhances interfacial adhesion, reduces interfacial tension, and improves compatibility.
[0049] Embodiment 1: In some embodiments, a method for preparing a substrate-like substrate for HDI process comprises the following steps:
[0050] Step 1: Preparation of glue.
[0051] (1) Preparation of hexagonal boron nitride and alumina gel
[0052] 1450 parts of hexagonal boron nitride and 120 parts of alumina were ground to nanoscale and dispersed in 1020 parts of 12.2w% sodium alginate aqueous solution. The mixture was then dripped dropwise into 2490 parts of 10w% calcium chloride aqueous solution under stirring conditions. At the same time, 250 parts of polyethyleneimine were added in 5 times, and the cross-linking reaction was carried out for 3.3 hours. The surface of the gel microbeads was then rinsed with deionized water twice, and 500 parts of 25w% citric acid aqueous solution were evenly sprayed on the surface of the gel microbeads. Finally, the hexagonal boron nitride and alumina gel microbeads were obtained after drying at a low temperature of 65°C.
[0053] (2) Dispersion of hexagonal boron nitride and alumina gel
[0054] First, 435 parts of PM (propylene glycol methyl ether) were added into the reactor, and the high-speed stirring was started at 1000 r / min. Then, 613 parts of hexagonal boron nitride and alumina gel were added. The addition must be done while stirring. After the addition is completed, the timing was started and the stirring was continued for 1.5 hours. The dispersion temperature was 30°C and the pressure was normal.
[0055] (3) Resin tank: 472 parts of toluene, 700 parts of BT resin (can be pre-dissolved in advance), 334 parts of o-methylphenolic epoxy resin, 2 parts of EPDM rubber, and 551 parts of PPO powder are added to the reactor;
[0056] (4) Fixing reaction: 7 parts of 2E4MZ and 5 parts of titanate coupling agent were added to the reactor, the reaction temperature was controlled at 45°C, and the reaction was continued at a high speed of 1000 r / min for 5 hours to allow the above resin to fully undergo a curing reaction;
[0057] (5) Stop the machine to measure S / G: Use a sampler to extract an appropriate amount of glue liquid to the laboratory to test the S / G (curing time) of the glue. If the S / G range is 280~320S, the glue quality is qualified;
[0058] Step 2: Preparation of prepreg.
[0059] The electronic-grade glass fiber cloth is placed on the cloth rack of the impregnation machine, and its advancement is controlled by tension. The electronic-grade glass fiber cloth passes through an impregnation tank with glue (the glue is pumped into the impregnation tank through a pipeline), and the electronic-grade glass fiber cloth soaked in glue enters an oven. The oven temperature is controlled at 240°C to evaporate excess solvent and perform further curing reaction. After drying, a semi-cured sheet (referred to as PP sheet) is obtained.
[0060] Step 3: Preparation of copper clad substrate for carrier-like substrate for HDI process.
[0061] The multi-layer prepreg and copper foil are stacked and placed in a hot press for hot pressing (temperature is 240℃, maximum pressure is 1.8Mpa). After the prepreg is hot pressed, the resin in the prepreg is melted by high temperature, and the bubbles are driven out under high pressure and the resin is completely solidified, completing the strong bonding between the PP sheets and the copper foil. According to the diffusion principle, this bonding is achieved through the mutual diffusion and penetration between the macromolecules on the interface, and then the interweaving is produced.
[0062] Embodiment 2: In some embodiments, a method for preparing a substrate-like substrate for HDI process comprises the following steps:
[0063] Step 1: Preparation of glue.
[0064] (1) Preparation of hexagonal boron nitride and alumina gel
[0065] 1380 parts of hexagonal boron nitride and 130 parts of alumina were ground to nanoscale and dispersed in 710 parts of 13.6w% sodium alginate aqueous solution. The mixture was then dripped dropwise into 2100 parts of 15w% calcium chloride aqueous solution under stirring conditions. At the same time, 380 parts of polyethyleneimine were added in three times and the cross-linking reaction was carried out for 2.5 hours. The surface of the gel microbeads was then rinsed with deionized water for three times, and 750 parts of 34w% citric acid aqueous solution were evenly sprayed on the surface of the gel microbeads. Finally, the hexagonal boron nitride and alumina gel microbeads were obtained after drying at a low temperature of 55°C.
[0066] (2) Dispersion of hexagonal boron nitride and alumina gel
[0067] First, 402 parts of PM (propylene glycol methyl ether) were added into the reactor, and the high-speed stirring was started at 2000 r / min. Then, 584 parts of hexagonal boron nitride and alumina gel were added. The addition must be done while stirring. After the addition is completed, the timing was started and the stirring was continued for 1.2 hours. The dispersion temperature was 45°C and the pressure was normal.
[0068] (3) Resin tank: 450 parts of toluene, 782 parts of BT resin (can be pre-dissolved in advance), 285 parts of o-methylphenolic epoxy resin, 4 parts of EPDM rubber, and 453 parts of PPO powder are added to the reactor;
[0069] (4) Fixing reaction: 4 parts of 2E4MZ and 7 parts of titanate coupling agent were added to the reactor, the reaction temperature was controlled at 30°C, and the reaction was continued at a high speed of 2000 r / min for 4.5 hours to allow the above resin to fully undergo a curing reaction;
[0070] (5) Stop the machine to measure S / G: Use a sampler to extract an appropriate amount of glue liquid to the laboratory to test the S / G (curing time) of the glue. If the S / G range is 280~320S, the glue quality is qualified;
[0071] Step 2: Preparation of prepreg.
[0072] The electronic-grade glass fiber cloth is placed on the cloth rack of the impregnation machine, and its advancement is controlled by tension. The electronic-grade glass fiber cloth passes through an impregnation tank with glue (the glue is pumped into the impregnation tank through a pipeline), and the electronic-grade glass fiber cloth soaked in glue enters an oven. The oven temperature is controlled at 180°C, excess solvent is evaporated, and further curing reaction is carried out. After drying, a semi-cured sheet (referred to as PP sheet) is obtained.
[0073] Step 3: Preparation of copper clad substrate for carrier-like substrate for HDI process.
[0074] The multi-layer prepreg and copper foil are stacked and placed in a hot press for hot pressing (temperature is 200℃, maximum pressure is 3.0Mpa). After the prepreg is hot pressed, the resin in the prepreg is melted by high temperature, and the bubbles are driven out under high pressure and the resin is completely solidified, completing the strong bonding between the PP sheets and the copper foil. According to the diffusion principle, this bonding is achieved through the mutual diffusion and penetration between the macromolecules on the interface, and then the interweaving is produced.
[0075] Embodiment 3: In some embodiments, a method for preparing a substrate-like substrate for HDI process comprises the following steps:
[0076] Step 1: Preparation of glue.
[0077] (1) Preparation of hexagonal boron nitride and alumina gel
[0078] 1396 parts of hexagonal boron nitride and 122 parts of alumina were ground to nanoscale and dispersed in 860 parts of 10.8w% sodium alginate aqueous solution. The mixture was then dripped dropwise into 2350 parts of 12w% calcium chloride aqueous solution under stirring conditions. At the same time, 320 parts of polyethyleneimine were added in 4 times and the cross-linking reaction lasted for 3 hours. The surface of the gel microbeads was then rinsed with deionized water for 3 times, and 650 parts of 28w% citric acid aqueous solution were evenly sprayed on the surface of the gel microbeads. Finally, the hexagonal boron nitride and alumina gel microbeads were obtained after drying at a low temperature of 60°C.
[0079] (2) Dispersion of hexagonal boron nitride and alumina gel
[0080] First, add 415 parts of PM (propylene glycol methyl ether) into the reactor, start high-speed stirring at 1800r / min, add 600 parts of hexagonal boron nitride and alumina gel, and add while stirring. Start timing after the addition is completed, stir for 1.3 hours, the dispersion temperature is 35°C, and the pressure is normal;
[0081] (3) Resin tank: 460 parts of toluene, 755 parts of BT resin (can be pre-dissolved in advance), 320 parts of o-methylphenolic epoxy resin, 3 parts of EPDM rubber, and 470 parts of PPO powder are added to the reactor;
[0082] (4) Fixing reaction: 5 parts of 2E4MZ and 6 parts of titanate coupling agent were added to the reactor, the reaction temperature was controlled at 35°C, and the reaction was continued at a high speed of 1500 r / min for 5 hours to allow the above resin to fully undergo a curing reaction;
[0083] (5) Stop the machine to measure S / G: Use a sampler to extract an appropriate amount of glue liquid to the laboratory to test the S / G (curing time) of the glue. If the S / G range is 280~320S, the glue quality is qualified;
[0084] Step 2: Preparation of prepreg.
[0085] The electronic-grade glass fiber cloth is placed on the cloth rack of the impregnation machine, and its advancement is controlled by tension. The electronic-grade glass fiber cloth passes through an impregnation tank with glue (the glue is pumped into the impregnation tank through a pipeline), and the electronic-grade glass fiber cloth soaked in glue enters an oven. The oven temperature is controlled at 200°C, excess solvent is evaporated, and further curing reaction is carried out. After drying, a semi-cured sheet (referred to as PP sheet) is obtained.
[0086] Step 3: Preparation of copper clad substrate for carrier-like substrate for HDI process.
[0087] The multi-layer prepreg and copper foil are stacked and placed in a hot press for hot pressing (temperature is 220℃, maximum pressure is 2.0Mpa). After the prepreg is hot pressed, the resin in the prepreg is melted by high temperature, and the bubbles are driven out under high pressure and the resin is completely solidified, completing the strong bonding between the PP sheets and the copper foil. According to the diffusion principle, this bonding is achieved through the mutual diffusion and penetration between the macromolecules on the interface, and then the interweaving is produced.
[0088] Embodiment 4: In some embodiments, a method for preparing a substrate-like substrate for HDI process comprises the following steps:
[0089] Step 1: Preparation of glue.
[0090] (1) Preparation of hexagonal boron nitride and alumina gel
[0091] 1395 parts of hexagonal boron nitride and 128 parts of alumina were ground to nanoscale and dispersed in 735 parts of 12.6w% sodium alginate aqueous solution. The mixture was then dripped dropwise into 2108 parts of 14w% calcium chloride aqueous solution under stirring conditions. At the same time, 375 parts of polyethyleneimine were added in three times, and the cross-linking reaction was carried out for 2.8 hours. The surface of the gel microbeads was then rinsed with deionized water for three times, and 600 parts of 32w% citric acid aqueous solution were evenly sprayed on the surface of the gel microbeads. Finally, the hexagonal boron nitride and alumina gel microbeads were obtained after drying at a low temperature of 58°C.
[0092] (2) Dispersion of hexagonal boron nitride and alumina gel
[0093] First, 405 parts of PM (propylene glycol methyl ether) were added into the reactor, and the high-speed stirring was started at 1900 r / min. Then, 590 parts of hexagonal boron nitride and alumina gel were added. The addition must be done while stirring. After the addition is completed, the timing was started and the stirring was continued for 1.6 hours. The dispersion temperature was 43°C and the pressure was normal.
[0094] (3) Resin tank: 455 parts of toluene, 780 parts of BT resin (can be pre-dissolved in advance), 295 parts of o-methylphenolic epoxy resin, 3.5 parts of EPDM rubber, and 455 parts of PPO powder are added to the reactor;
[0095] (4) Fixing reaction: 4.5 parts of 2E4MZ and 6.8 parts of titanate coupling agent were added to the reactor, the reaction temperature was controlled at 32°C, and the reaction was continued at a high speed of 1800 r / min for 4.8 hours to allow the above resin to fully undergo a curing reaction;
[0096] (5) Stop the machine to measure S / G: Use a sampler to extract an appropriate amount of glue liquid to the laboratory to test the S / G (curing time) of the glue. If the S / G range is 280~320S, the glue quality is qualified;
[0097] Step 2: Preparation of prepreg.
[0098] The electronic-grade glass fiber cloth is placed on the cloth rack of the impregnation machine, and its advancement is controlled by tension. The electronic-grade glass fiber cloth passes through an impregnation tank with glue (the glue is pumped into the impregnation tank through a pipeline), and the electronic-grade glass fiber cloth soaked in glue enters an oven. The oven temperature is controlled at 185°C to evaporate excess solvent and perform further curing reaction. After drying, a semi-cured sheet (referred to as PP sheet) is obtained.
[0099] Step 3: Preparation of copper clad substrate for carrier-like substrate for HDI process.
[0100] The multi-layer prepreg and copper foil are stacked and placed in a hot press for hot pressing (temperature is 230℃, maximum pressure is 2.5Mpa). After the prepreg is hot pressed, the resin in the prepreg is melted by high temperature, and the bubbles are driven out under high pressure and the resin is completely solidified, completing the strong bonding between the PP sheets and the copper foil. According to the diffusion principle, this bonding is achieved through the mutual diffusion and penetration between the macromolecules on the interface, and then the interweaving is produced.
[0101] Comparative Example 1: The difference from Example 4 is that the preparation method of hexagonal boron nitride and alumina gel is different: 1395 parts of hexagonal boron nitride and 128 parts of alumina are ground to nanoscale and dispersed in 735 parts of 12.6w% sodium alginate aqueous solution, and then the mixed solution is dripped dropwise into 2108 parts of 14w% calcium chloride aqueous solution under stirring conditions, and 375 parts of polyethyleneimine are added in 3 times, and the cross-linking reaction is carried out for 2.8h; then the surface of the gel beads is rinsed with deionized water 3 times, and finally dried at a low temperature of 58°C to obtain hexagonal boron nitride and alumina gel beads.
[0102] Comparative Example 2: The difference from Example 4 is that the preparation method of hexagonal boron nitride and alumina gel is different: 1395 parts of hexagonal boron nitride and 128 parts of alumina are ground to nanoscale and dispersed in 735 parts of 12.6w% sodium alginate aqueous solution, and then the mixed solution is dripped dropwise into 2108 parts of 14w% calcium chloride aqueous solution under stirring conditions, and the cross-linking reaction is carried out for 2.8h; then the surface of the gel microbeads is rinsed with deionized water 3 times, and 600 parts of 32w% citric acid aqueous solution are evenly sprayed on the surface of the gel microbeads, and finally dried at a low temperature of 58°C to obtain hexagonal boron nitride and alumina gel microbeads.
[0103] Comparative Example 3: The difference from Example 4 is that the ratio of glue raw materials is different: 405 parts of PM, 500 parts of hexagonal boron nitride and alumina gel, 455 parts of toluene, 870 parts of BT resin, 295 parts of o-methylphenolic epoxy resin, 3.5 parts of EPDM rubber, 455 parts of PPO powder, 4.5 parts of 2E4MZ, and 6.8 parts of titanate coupling agent.
[0104] Comparative Example 4: The difference from Example 4 is that the ratio of glue raw materials is different: 405 parts of PM, 700 parts of hexagonal boron nitride and alumina gel, 455 parts of toluene, 670 parts of BT resin, 295 parts of o-methylphenolic epoxy resin, 3.5 parts of EPDM rubber, 455 parts of PPO powder, 4.5 parts of 2E4MZ, and 6.8 parts of titanate coupling agent.
[0105] Test Examples The following performance tests were performed on the copper-clad substrates for carrier-like substrates for HDI process prepared in Examples 1 to 4 and Comparative Examples 1 to 4:
[0106] Thermal conductivity: ASTM D5470-17;
[0107] Dielectric properties (dielectric constant Dk, dielectric loss Df): IPC-TM-650 2.5.5.9:1998;
[0108] CTE (Coefficient of Thermal Expansion): IPC-TM-650 2.4.24C:1994;
[0109] Heat resistance: thermal cracking time T288 / T260: IPC-TM-650 2.4.24.C: 1994; glass transition temperature Tg: IPC-TM-650 2.4.24.
[0110] Strength (peel strength, bending strength): GB / T 4723-2017.
[0111] Board warping: IPC-TM-650.
[0112] Table 1 Performance test results of copper clad substrate for HDI process
[0113] Test items Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Thermal conductivity 1.98W / mk 1.90W / mk 1.96W / mk 1.94W / mk T288 >80min >80min >80min >80min X / Y-CTE(<Tg) 11.3ppm / ℃ 12.0ppm / ℃ 11.6ppm / ℃ 12.1ppm / ℃ Z-CTE(α1 / α2) 20 / 101ppm / ℃ 25 / 115ppm / ℃ 22 / 108ppm / ℃ 21 / 103ppm / ℃ Dk(10GHZ,R / C50%) 3.7 3.9 3.5 3.7 Df(10GHZ,R / C50%) 0.004 0.003 0.004 0.003 Tg 220℃ 221℃ 220℃ 223℃ Peel strength 1.95N / mm 1.90N / mm 1.99N / mm 1.92N / mm Bending Strength 318.5MPa 301.7MPa 312.6MPa 309.1MPa Plate bending 0.15mm 0.13mm 0.14mm 0.13mm
[0114] Table 2 Performance test results of copper clad substrate for HDI process
[0115] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Thermal conductivity 1.90W / mk 1.88W / mk 1.09W / mk 1.65W / mk T288 >80min >80min >60min >60min X / Y-CTE(<Tg) 12.8ppm / ℃ 12.3ppm / ℃ 13.5ppm / ℃ 13.9ppm / ℃ Z-CTE(α1 / α2) 25 / 122ppm / ℃ 22 / 117ppm / ℃ 28 / 135ppm / ℃ 30 / 182ppm / ℃ Dk(10GHZ,R / C50%) 3.9 4.7 4.3 5.2 Df(10GHZ,R / C50%) 0.005 0.005 0.004 0.006 Tg 215℃ 211℃ 200℃ 223℃ Peel strength 1.81N / mm 1.70N / mm 1.55N / mm 1.75N / mm Bending Strength 298.5MPa 276.4MPa 301.9MPa 312.3MPa Plate bending 0.18mm 0.34mm 0.41mm 0.28mm
[0116] The invention first prepares hexagonal boron nitride and alumina gel, disperses the hexagonal boron nitride and alumina in a sodium alginate aqueous solution, then drips the gel into a calcium chloride aqueous solution, and simultaneously adds polyethyleneimine for cross-linking reaction, so that the hexagonal boron nitride and alumina are modified by sodium alginate, calcium chloride and polyethyleneimine to form gel microbeads with enhanced network structure, rinses the surface of the gel microbeads and then uses a citric acid aqueous solution to evenly spray the surface of the gel microbeads, so that the citric acid and the metal ions on the surface of the network structure of the gel microbeads are coordinated to form a stable complex, and then the obtained hexagonal boron nitride and alumina gel are dispersed in a resin system, and a titanate coupling agent is added. A sufficient curing reaction is carried out; a semi-cured sheet is then prepared, and then a copper-clad substrate for a carrier-like substrate for HDI process is prepared; the prepared copper-clad substrate for a carrier-like substrate for HDI process can simultaneously meet the requirements of electronic products for excellent heat resistance (reaching the level of high Tg packaging substrates), low thermal expansion coefficient, high thermal conductivity (thermal conductivity can reach 1.98W / mk) and low dielectric (dielectric constant Dk is at least 3.5, dielectric loss Df is at least 0.003) and other requirements, and has high strength (peel strength is at most 1.99N / mm, bending strength is at most 318.5MPa), and small board warping (board warping is at least 0.13mm).
[0117] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carrier-like substrate for HDI process, characterized in that BT resin and o-methylphenolic epoxy resin are compounded and modified as the main resin of the substrate, and hexagonal boron nitride and alumina gel obtained by modification are added to the resin system to make glue; then the glue and glass fiber cloth are impregnated and baked to obtain a prepreg, and finally the prepreg is subjected to hot pressing to obtain a copper foil substrate for the carrier-like substrate for HDI process; The glue comprises the following raw materials in parts by weight: 700-782 parts of BT resin, 285-334 parts of o-methylphenolic epoxy resin, 453-551 parts of PPO powder, 402-435 parts of solvent A, 450-472 parts of solvent B, 584-613 parts of hexagonal boron nitride and alumina gel, 5-7 parts of coupling agent, 2-4 parts of EPDM rubber, and 4-7 parts of accelerator; The hexagonal boron nitride and alumina gel comprises the following raw materials in parts by weight: 138-145 parts of hexagonal boron nitride, 12-13 parts of alumina, 71-102 parts of 10.8-13.6w% sodium alginate aqueous solution, 210-249 parts of 10-15w% calcium chloride aqueous solution, 50-75 parts of 25-34w% citric acid aqueous solution, and 25-38 parts of polyethyleneimine.
2. The substrate-like substrate for HDI process according to claim 1, characterized in that: The preparation method of the hexagonal boron nitride and alumina gel is as follows: grinding hexagonal boron nitride and alumina to nanometer scale and dispersing them in a sodium alginate aqueous solution, then dripping the mixed solution drop by drop into a calcium chloride aqueous solution under stirring conditions, and adding polyethyleneimine in 3 to 5 times, and performing a cross-linking reaction for 2.5 to 3.3 hours; then washing the surface of the gel microbeads with deionized water for 2 to 3 times, spraying the surface of the gel microbeads with a citric acid aqueous solution, and finally drying at a low temperature of 55 to 65° C. to obtain the hexagonal boron nitride and alumina gel microbeads.
3. The substrate-like substrate for HDI process according to claim 2, characterized in that: The promoter is 2E4MZ, the solvent A is PM, the solvent B is toluene, and the coupling agent is titanate coupling agent.
4. A method for preparing a substrate-like substrate for HDI process according to claim 1, characterized in that: The following steps are involved: Step 1: Preparation of glue; (1) Preparation of hexagonal boron nitride and alumina gel Grind hexagonal boron nitride and alumina to nanometer scale and disperse them in sodium alginate aqueous solution, then drip the mixture drop by drop into calcium chloride aqueous solution under stirring conditions, and add polyethyleneimine in 3 to 5 times, and cross-link for 2.5 to 3.3 hours; then rinse the surface of the gel microbeads with deionized water, spray the surface of the gel microbeads with citric acid aqueous solution, and finally dry to obtain hexagonal boron nitride and alumina gel microbeads; (2) Dispersion of hexagonal boron nitride and alumina gel First, inject solvent A into the reactor, stir at high speed, add hexagonal boron nitride and alumina gel, and stir while adding. Start timing after the addition is completed, stir for more than 1 hour, the dispersion temperature is 30-45℃, and the pressure is normal; (3) Resin tank: Solvent B, BT resin, o-methylphenolic epoxy resin, EPDM rubber, and PPO powder are then pumped into the reactor; (4) Fixing reaction: Add the accelerator and coupling agent into the reaction kettle, control the reaction temperature at 30-45°C, and continue to stir at high speed for 4.5-5 hours to allow them to fully react with the above resin to produce a curing reaction; (5) Stop the machine to measure S / G: Draw an appropriate amount of glue liquid and test whether the S / G of the glue is between 280 and 320S. If so, the glue quality is qualified; Step 2: Preparation of prepreg; The glass fiber cloth is immersed in the prepared glue and then dried to obtain a semi-solid sheet with appropriate parameters; Step 3: Preparation of copper clad substrate for carrier-like substrate for HDI process; The multi-layer prepreg and copper foil are stacked and placed in a hot press for hot pressing. The prepreg is hot pressed to melt the resin in the prepreg and drive out the bubbles under high pressure, so that the resin gradually hardens and adheres to the copper foil.
5. The method for preparing a substrate-like substrate for HDI process according to claim 4, characterized in that: The high-speed stirring speed is controlled at 1000-2000r / min.
6. The method for preparing a substrate-like substrate for HDI process according to claim 5, characterized in that: In step (1), the surface of the gel microbeads is rinsed with deionized water for 2 to 3 times, a citric acid aqueous solution is evenly sprayed on the surface of the gel microbeads, and finally dried at a low temperature of 55 to 65° C. to obtain hexagonal boron nitride and alumina gel microbeads.
7. The method for preparing a substrate-like substrate for HDI process according to claim 6, characterized in that: Step 2 is specifically as follows: placing the electronic-grade glass fiber cloth on the cloth rack of the impregnation machine, controlling its advancement by tension, passing the electronic-grade glass fiber cloth through the impregnation tank with glue, and the electronic-grade glass fiber cloth soaked in glue enters the oven, controlling the oven temperature to 180-240°C, and obtaining a semi-cured sheet after drying.
8. The method for preparing a substrate-like substrate for HDI process according to claim 7, characterized in that: The hot pressing treatment temperature in step 3 is 200-240° C. and the pressure is 1.8-3.0 MPa.
9. A substrate-like substrate for HDI process prepared according to the preparation method of claim 8.
10. Use of a substrate-like substrate for an HDI process according to any one of claims 1 to 3 in preparing a substrate-like substrate for a 5G high-speed HDI process.